PKM Pengolahan Limbah Ternak Menjadi Biochar - Yohanes Parlindungan Situmeang; I Dewa Nyoman Sudita (Postgraduated Community Service Journal, 2021)
Biochar is a material rich in carbon with the physical characteristics of porous biochar morphology. Biochar has the ability to retain nutrients and water, increase microbial life in the soil and overall increase soil fertility. Animal waste that often pollutes the environment can be converted into biochar through incomplete combustion to produce biochar charcoal which can be used to improve nutrient-poor agricultural soils. This service is carried out at the Satwa Winangun livestock farmer group, Tangkas Village, Klungkung Regency which takes place from May to July 2021. This PKM activity aims to increase the understanding and skills of partners to innovate in processing livestock waste into biochar. The method used to achieve this goal is through training, mentoring, and technology transfer with direct practice in the field. The transfer of technology for making biochar from animal waste received a good response from the trainees, especially because they had never made biochar. Through group strengthening and technology transfer with the PKM program, the trainees have been able to practice directly the process of making biochar and producing biochar fertilizer products that are ready to be applied to agricultural land.